The yield and volatility of automobile industry under the rapid changes in crude oil prices - Xiang, Shang (BCP Business & Management, 2022)
The increasing conflict between Russia and Ukraine since February 2022 has had a significant effect on the world's political and economic condition. In the early days of the conflict, crude oil prices were subject to extreme swings. The auto industry is impacted as it is a part of the macroeconomy and is closely linked to the oil sector. This essay intends to investigate how changes in crude oil prices brought on by the war between Russia and Ukraine affect both the traditional and the new energy auto industries. The modeling, analysis, and probable explanation of the fall in new energy vehicle stock returns brought on by the rise in crude oil prices, which is contrary to economic intuition, are the research contributions of this work.